Community Pharmacy Practice during COVID-19 Pandemic in Pokhara Metropolitan City, Nepal - Khanal, D.P.; Mishra, S. (Journal of Manmohan Memorial Institute of Health Sciences, 2021)
Background: Pharmacist being a member of health care team served as a front-liner to provide health care service in the community as it is the first place visited by most of the people to purchase medicine and receive treatment or advice for minor illness. Objectives: The objectives of this study were to assess the community pharmacy and their practitioners experience during Covid-19 pandemic including barriers to activities, preventive measures adopted and service offered by them in Pokhara metropolitan city. Method: A cross-sectional descriptive study was design using purposive sampling technique and data from 115 community pharmacies inside Pokhara metropolitan city (1-33 wards) were collected using both close-ended and open-ended questionnaires. Results: Majority respondents are young having experience 2-5 years. Assistant pharmacists with Diploma in pharmacy degree were 44 % and more than half of respondents were both owner and pharmacist themselves. Major barriers during Covid-19 pandemics were: shortage of personal protective equipments, panic of the patients, and shortage of products. Only 53% followed preventive measures related to Covid-19 pandemics. This was dangerous and risk factor for infection transmission. Due to the fear of pandemic, most pharmacies are providing limited pharmaceutical service. The patient suspected with Covid-19 was referred to hospital and some patients were just given medicine as per their symptoms with the fear of getting infection. Conclusion: Community pharmacists were not following the preventive measures sufficiently which may cause high chance of community transmission of Covid-19 in Pokhara metropolitan city.